2008
DOI: 10.1111/j.1462-2920.2008.01675.x
|View full text |Cite
|
Sign up to set email alerts
|

Power output and columbic efficiencies from biofilms of Geobacter sulfurreducens comparable to mixed community microbial fuel cells

Abstract: It has been previously noted that mixed communities typically produce more power in microbial fuel cells than pure cultures. If true, this has important implications for the design of microbial fuel cells and for studying the process of electron transfer on anode biofilms. To further evaluate this, Geobacter sulfurreducens was grown with acetate as fuel in a continuous flow 'ministack' system in which the carbon cloth anode and cathode were positioned in close proximity, and the cation-selective membrane surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
334
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(377 citation statements)
references
References 38 publications
27
334
1
1
Order By: Relevance
“…DL-1 was grown from frozen 50% dimethyl sulfoxide stocks (generated from cultures provided by D. Lovley, UMass Amherst) in sterile sealed tubes containing 10 ml of freshwater media degassed with a N 2 / CO 2 (80/20) gas mixture 22,39 . All transfers were performed in the 80/20 gas mix.…”
Section: Methodsmentioning
confidence: 99%
“…DL-1 was grown from frozen 50% dimethyl sulfoxide stocks (generated from cultures provided by D. Lovley, UMass Amherst) in sterile sealed tubes containing 10 ml of freshwater media degassed with a N 2 / CO 2 (80/20) gas mixture 22,39 . All transfers were performed in the 80/20 gas mix.…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies examined bacterial diversity from 16S rDNA clone libraries, which reflect bacterial diversity at a single point in time, typically at the end of the incubations. More recent studies have shown qualitative changes in diversity do occur over time, and that power output from mixed microbial assemblages may be greater than pure cultures (Rabaey and Verstraete, 2005;Nevin et al, 2008). Quantitative changes in microbial processes in relation to MFC performance, however, have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Studies are demonstrating that any compound degradable by bacteria can be converted into electricity [20]. The range of compounds include, but by no means limited to, acetate [21,22], glucose [23], starch [24], cellulose [25], wheat straw [26], pyridine [27], phenol [28], p-nitrophenol [29] and complex solutions such as domestic waste water [30,31], brewery waste [32], land file leachate [33], chocolate industry waste [34], mixed fatty acids [35] and petroleum contaminates [36]. Within these systems less biomass is also generally produced then their equivalent aerobic processes and without the need for an energy intensive aeration process less energy is required [7].…”
Section: Potential Applications For Microbial Fuel Cellsmentioning
confidence: 99%